2007
DOI: 10.1038/sj.ijo.0803630
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of diabetes reversibility after bariatric surgery

Abstract: Objective: Insulin resistance is a strong biological marker of both obesity and type 2 diabetes. Abnormal fat deposition within skeletal muscle has been identified as a mechanism of obesity-associated insulin resistance. Biliopancreatic diversion (BPD), inducing a massive lipid malabsorption, leads to a reversion of type 2 diabetes. To elucidate the mechanisms of diabetes reversibility, the expression of genes involved in glucose and free fatty acids (FFAs) metabolism was investigated in skeletal muscle biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 50 publications
(46 reference statements)
2
3
0
2
Order By: Relevance
“…27,50,51,93,94,96,112,113,128–138 The results from these studies demonstrate that skeletal muscle insulin sensitivity does not change after moderate (~10%) weight loss, 2–4 weeks after RYGB surgery, 50,51 but increases markedly after greater (20%–40%) weight loss, 6–16 months after surgery. 50,128–132,134,137 A similar improvement in insulin sensitivity (~150%) has been reported after marked weight loss (~33%) induced by vertical banded gastroplasty. 136 In addition, we have found that 20% weight loss induced by either LAGB or RYGB causes nearly a two-fold increase in skeletal muscle insulin sensitivity, assessed by using the HEC procedure in conjunction with stable isotopically-labeled tracer infusion, but there was no difference between the two surgical groups.…”
Section: Effect Of Bariatric Surgery On Insulin Sensitivitysupporting
confidence: 69%
“…27,50,51,93,94,96,112,113,128–138 The results from these studies demonstrate that skeletal muscle insulin sensitivity does not change after moderate (~10%) weight loss, 2–4 weeks after RYGB surgery, 50,51 but increases markedly after greater (20%–40%) weight loss, 6–16 months after surgery. 50,128–132,134,137 A similar improvement in insulin sensitivity (~150%) has been reported after marked weight loss (~33%) induced by vertical banded gastroplasty. 136 In addition, we have found that 20% weight loss induced by either LAGB or RYGB causes nearly a two-fold increase in skeletal muscle insulin sensitivity, assessed by using the HEC procedure in conjunction with stable isotopically-labeled tracer infusion, but there was no difference between the two surgical groups.…”
Section: Effect Of Bariatric Surgery On Insulin Sensitivitysupporting
confidence: 69%
“…In these studies, HOMA and glucose disposal improved significantly [ 35 – 38 ]. The improvement we see at 1mU/kg/min is of similar magnitude to that reported in other studies [ 37 ], however our study is the first to undertake a detailed examination across a range of plasma insulin concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this hypothesis is the fact that bilio-pancreatic diversion (BPD), an operation that involves the greatest length of intestinal bypass (the duodenum and jejunum in their entirety) is associated with the best rates of long-term remission of diabetes (5,12). BPD results in major improvement of skeletal muscle S I , mediated by changes in the expression of genes that regulate glucose and fatty acid metabolism in response to nutrient availability (43).…”
Section: Discussionmentioning
confidence: 78%